KAJIAN YURIDIS TENTANG KESEPAKATAN ADAT DALAM PERKAWINAN SUKU SABU DI KOTA KUPANG - Sodak, Frederika Atalia; Nubatonis, Orpa J; Dju Bire, Chatryen M (Petitum Law Journal, 2025)
This research is titled "Legal Study on Customary Agreements in Marriage of the Sabu Tribe in Kupang City". The objective of this research is to understand the background of customary agreements built in the implementation of Sabu tribal marriage and the legal consequences that arise. The method used is empirical legal research with a qualitative approach, involving interviews with relevant parties. The research results show that customary agreements in Sabu tribal marriage are heavily influenced by cultural values and traditions passed down through generations. Processes such as matchmaking and parental introductions serve as symbols of commitment and mutual understanding. In addition, customary agreements also have significant legal consequences, which include social legitimacy and legal protection for the rights of couples. This research recommends that the Sabu tribal community preserve their marriage traditions and that the government strengthen the recognition of customary law within the national legal framework. In this way, customary agreements are expected to be integrated with existing legal developments, maintaining cultural identity while remaining relevant to the changing times.